ANALISIS REAKSI INVESTOR PASCA PENGUMUMAN DITETAPKAN PANDEMI COVID TERHADAP PERGERAKAN SAHAM (Studi kasus pada perusahaan sub sektor makanan dan minuman yang terdaftar di BEI periode 2020) - Erya Santi Safitri; Junaidi Junaidi; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to find out how investors react to stock price movements before and after the COVID-19 pandemic. This study uses an event study on food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2020. The time of the study lasted for 10 days, namely 5 days before the covid-19 pandemic and 5 days after the covid-19 pandemic. Samples obtained as many as 30 companies. In this study using a different test. The results of this study are based on the results of the Wilcoxon test, there is no difference in abnormal returns before and after the announcement of the covid-19 pandemic and there is no difference in investor reactions before and after the announcement of the covid-19 pandemic.Keywords: Investor reaction, abnormal return, TVA.